La Leishmaniosis - Jorge R. Rey (EDIS)
ENY-738S, a 5-page illustrated fact sheet by Jorge R. Rey, is the Spanish language version of ENY-738: Leishmaniasis. It describes this disease caused by parasitic protozoans transmitted to humans by sandflies. Includes description of the parasite, forms and symptoms, distribution, treatment, coinfection with HIV/AIDS and references. Published by the UF Department of Entomology and Nematology, June 2007.